Development of worksheet based on high-order thinking skills to improve high-order thinking skills of the students - Yennita Yennita; Isra Khasyyatillah; Gibran Gibran; Mitri Irianti (Universitas Riau, 2018)
This research aimed to develop high order thinking skills workheet in momentum, impulse, and collision topic for senior high school This type of research is Research and Development follow 4D models, includes : define, design, develop and disseminate. Data collection instruments used validation sheets for given to 5 validator, Aspects assessed include graphic, presentation, language, and the contents of workheet. Based on the result of data analysis showed that all aspects got average score in the range of 3.4 to 4 with categories of very high. Thus, high order thinking skills was valid. For the purposes of testing the worksheet is given on 68 students. to measure the effectiveness of worksheet used Higher Level Thinking Ability Test that amounts to 12 items. Based on the result of data analysis indicate, There is difference of higher order thinking skill of students who use HOTS worksheet than who are not use HOTS worksheet, where the average Higher Order Thinking Skill on students who use HOTS worksheet higher